Co0.2Fe2.8O4/C composite nanofibers with designable 3D hierarchical architecture for high-performance electromagnetic wave absorption. Issue 16 (15th August 2021) - Wang, Yongpeng; Zhang, Yingyuan; Tao, Jianan; Sun, Wei; Liu, Mengzhu; Cui, Xuejun; Zhang, Haibo; Jiang, Zhenhua
Abstract: High-performance electromagnetic (EM) wave absorption property could be achieved by architecture design of nanomaterials. Herein, two layer hybrid Co0.2 Fe2.8 O4 /carbon nanofibers with porous three-dimensional (3D) hierarchical structure were synthesized successfully through facile electrospinning, carbonization and mild chemical treatment. The Co0.2 Fe2.8 O4 particles grew along the carbon nanofibers, forming the enhanced heterogeneous interfaces and high specific areas. As expected, the EM wave absorbent showed an excellent absorbing capability. The composites achieved a maximum reflection loss (RL) of −43.45 dB at 11.1 GHz with thickness of 3.0 mm. More importantly, the effective bandwidth (RL ≤ −10dB) was 5.85 GHz, covering 30% of the entire measured bandwidth. The absorption intensity and bandwidth were superior to other typical CoFe-based composites. The intrinsic mechanism of the absorption revealed that the polarization losses, magnetic losses, magnetic natural resonance and exchanged resonance losses contributed to the high-performance microwave absorption. Moreover, good impedance matching and complex transmission paths that generated from unique porous network also played an important role. This study is expected to guide future exploration on designing and synthesizing high performance EM wave absorbents.